Antiviral and antioxidant properties of active alginate edible films containing phenolic extracts. (August 2018) - Fabra, María José; Falcó, Irene; Randazzo, Walter; Sánchez, Gloria; López-Rubio, Amparo
Abstract: In this work, novel active edible films having antiviral activity were developed through the solvent casting method. Emulsified edible films were prepared by adding lipids into alginate films in order to improve their water vapour permeability. In addition, two natural extracts rich in phenolic compounds, specifically a green tea extract (GTE) and a grape seed extract (GSE) were used as active agents. Interestingly, incorporating GTE or GSE within the biopolymer matrix, the films exhibited significant antiviral activity against murine norovirus (MNV) and hepatitis A virus (HAV) since ∼2 log reduction were recorded for the 0.75 g extract/g alginate in the film, being GTE more efficient than GSE. Furthermore, the incorporation of phenolic compounds imparted antioxidant capacity to the active films, showing 14.79 ± 0.25 and 3.50 ± 0.25 mM Trolox⋅ g extract in the film −1 for 0.75 GTE and 0.75 GSE films, respectively. It was also found that water barrier efficiency improved upon addition of the highest amount of GTE or GSE (1:0.75 alginate:extract ratio) which was ascribed to molecular interactions between the films' components, as demonstrated by infrared spectroscopy assays. These results reveal the potential of these active films, mainly the ones containing GTE, to improve food quality and safety. Graphical abstract: Image 1 Highlights: Green tea extract (GTE) and grape seed extract (GSE) were used to develop active films. Alginate-lipid edible films containing GTE or GSE showed antioxidant properties. Alginate-lipid films containing GTE or GSE exhibited antiviral activity against MNV and HAV. GTE was more efficient than GSE. WVP of alginate-lipid films improved upon addition of the highest amount of extracts.